Thyroid Screening in Early Pregnancy: Pros and Cons - Taylor, Peter N.; Zouras, Stamatios; Min, Thinzar; Nagarahaj, Kalyani; Lazarus, John H.; Okosieme, Onyebuchi (Frontiers in Endocrinology, 2018)
Universal thyroid screening in pregnancy is a key debate in thyroidology and obstetrics. It is well established that thyroid hormones are essential for maintaining pregnancy and optimal fetal development. Thyroid dysfunction is common in women of child-bearing age and also results in substantial adverse obstetric and child neurodevelopmental outcomes. Furthermore, thyroid dysfunction is readily diagnosed with reliable blood tests and easily corrected with inexpensive and available treatments. Screening only high-risk patients appears to miss the majority of cases and economic models show that compared to high-risk screening, universal screening is cost effective even if only overt hypothyroidism was assumed to have adverse obstetric effects. As a result, several countries now implement universal screening. Opponents of universal thyroid screening argue that asymptomatic borderline thyroid abnormalities such as subclinical hypothyroidism and isolated hypothyroxinemia form the bulk of cases of thyroid dysfunction seen in pregnancy and that there is a lack of high quality evidence to support their screening and correction. This review critically appraises the literature, examines the pros and cons of universal thyroid screening using criteria laid down by Wilson and Jungner. It also highlights the growing evidence for universal thyroid screening and indicates the key challenges and practicalities of implementation.